Dimensions of a community-based literacy program - Gan, Jennica I. (College of Education, University of the Philippines Diliman, 2019)
With the idea that only limited studies deal with literacy programs in informal settings, this study using a mixed methods approach investigated the dimensions of the Balsa Basa community-based literacy programs (CBLP) of Brgy. San Jose, Donsol, Sorsogon, Bicol. Particularly, it sought to determine what the Balsa Basa CBLP is, how it was developed and implemented, and how it transformed the readership of the students in terms of reading attitude and leisure reading. It also looked into the literacy practices of the parents, the teachers, and the programs leaders and how they view themselves as readers. Through deep engagement with the community over a span of three months, the program implementation was observed, workshops, interviews, and surveys with the community members were conducted, and archival research was executed. Analyses of data gathered show that the Balsa Basa CBLP is a program that envisions its students to become readers through its various activities such as Balsa Basa, Walk for Knowledge, reading time, among others and through the collaborative efforts of its community members from parents, teachers to Barangay officials. In developing and implementing the program, several key features were found evident: informal process, community-centeredness, community involvement, and strong sense of commitment. Having been implemented for more than five years, the program has positively transformed the following subcomponents of students readership: (a) reading attitude at home, (b) reading attitude in school, (c) goals for reading, (d) self-concept as readers, (e) types of materials read, (f) circumstances when they read, (g) places where they read, and (h) how they obtain their reading materials. Focusing on the programs key players, the parents, the teachers, and the program leaders in the community have different concepts of literacy, views of the uses of literacy, and ways of engaging in literacy. It shows that, although they are all involved in the same program, the literacy practices of the key players are diverse as influenced by their own distinct contexts. Similarly, these three groups of keys players have different views of themselves as readers. To sum up all the dimensions of a community-based literacy program, a conceptual framework was made to present the various parts and features of such program: (a) the literacy/readership goal that sets the direction of the program; (b) the activities that are carried out to meet the programs goal through reading engagements, supply of materials, and student empowerment; (c) the key players, including program leaders, teachers, parents, and other actors, who work together for the attainment of the goal; and (d) the key features (i.e community-centeredness, community involvement, and strong sense of commitment) for developing and implementing a community-based literacy program. Based on all of these findings, it is recommended that more community-based literacy programs be developed in other settings to help address the literacy needs of the students.